2002
DOI: 10.1577/1548-8675(2002)022<1340:rammll>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Rescinding a 254-mm Minimum Length Limit on White Crappies at Ft. Supply Reservoir, Oklahoma: The Influence of Variable Recruitment, Compensatory Mortality, and Angler Dissatisfaction

Abstract: A 254‐mm minimum length limit on crappies Pomoxis spp. was implemented on January 1, 1990, in Ft. Supply Reservoir, Oklahoma, to improve population size and age structure and angler catch rates but was rescinded 6 years later because of angler complaints. Before the regulation, the population was characterized by fast‐growing and short‐lived white crappies P. annularis; the spring fishery was supported by age‐2 fish. Size structure fluctuated widely before the length limit was implemented, ranging from 1% to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…Indeed, this was reported in several empirical studies (e.g., Anderson and Nehring, 1984;Novinger, 1987;Cornelius and Margenau, 1999;Newman and Hoff, 2000). However, other studies have found that total catch-and-release regulations or more stringent size or daily bag limits may result in reduced angler effort despite similar or increased catch rates (e.g., Muoneke, 1994;Almodóvar and Nicola, 1998;Boxrucker, 2002;Hurley and Jackson, 2002;Parker et al, 2007). Similarly, restrictive fly-only regulations that prohibited the use of organic bait were also been found to reduce angling pressure on a trout stream (Shetter and Alexander, 1962).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, this was reported in several empirical studies (e.g., Anderson and Nehring, 1984;Novinger, 1987;Cornelius and Margenau, 1999;Newman and Hoff, 2000). However, other studies have found that total catch-and-release regulations or more stringent size or daily bag limits may result in reduced angler effort despite similar or increased catch rates (e.g., Muoneke, 1994;Almodóvar and Nicola, 1998;Boxrucker, 2002;Hurley and Jackson, 2002;Parker et al, 2007). Similarly, restrictive fly-only regulations that prohibited the use of organic bait were also been found to reduce angling pressure on a trout stream (Shetter and Alexander, 1962).…”
Section: Discussionmentioning
confidence: 85%
“…Recent trends in recreational fisheries regulations have been toward reducing daily creel limits (Webb and Ott 1991;Jacobson 2005) and implementing lengthbased regulations (Boxrucker 2002;Paukert et al 2002;Isermann et al 2007). Creel limits can work to reduce harvest, but they are often too liberal to reduce harvest mortality (Cook et al 2001;Isermann et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Crappie anglers prefer catching large fish over catching many small fish (Petering et al. ; Allen and Miranda ), and satisfaction with crappie fisheries is often low (Boxrucker ). Fisheries managers have long sought to improve the size structure of crappie populations and yield from crappie fisheries by applying MLLs and daily limits (Colvin ; Allen and Miranda ; Maceina et al.…”
mentioning
confidence: 99%
“…In turn, slow growth rates cause reduced harvest rates (Hale et al. ; Bister ) and lower angler satisfaction (Boxrucker ). Thus, crappie MLLs are not universally successful and little guidance to fisheries managers exists on the use of MLLs for crappie fisheries.…”
mentioning
confidence: 99%